2022
DOI: 10.3390/f13091343
|View full text |Cite
|
Sign up to set email alerts
|

The Change in Growth, Osmolyte Production and Antioxidant Enzymes Activity Explains the Cadmium Tolerance in Four Tree Species at the Saplings Stage

Abstract: Phytoremediation is a green technology; however, very few species of arid environments have been identified as hyperaccumulators and fast growers. Therefore, a greenhouse experiment was performed to evidence the phytoaccumulation potential of Conocarpus erectus, Syzygium cumini, Populus deltoides and Morus alba at the sapling stage. Six-month-old plant saplings were subjected to control (CK; 0 µM) and cadmium treatments (Cd; CdCl2; 200 µM). The results depicted that plant growth, dry biomass production (leaf a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The existence of a higher concentration of heavy metals in the soil leads to a bigger toxicity to plants and greatly affects the plant biomass. The total biomass of organisms under the presence of the Cd stress could be significantly decreased [ 25 ]. Zhang et al [ 26 ] found that inoculation with different PGPRs could promote the growth and photosynthesis of P. praeruptorum to different degrees, thereby improving its tolerance to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a higher concentration of heavy metals in the soil leads to a bigger toxicity to plants and greatly affects the plant biomass. The total biomass of organisms under the presence of the Cd stress could be significantly decreased [ 25 ]. Zhang et al [ 26 ] found that inoculation with different PGPRs could promote the growth and photosynthesis of P. praeruptorum to different degrees, thereby improving its tolerance to the environment.…”
Section: Discussionmentioning
confidence: 99%